2018
DOI: 10.1002/hed.25072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative immunonutrition on postoperative short‐term outcomes of patients with head and neck squamous cell carcinoma

Abstract: Patients receiving preoperative immunonutrition had a shorter hospital LOS and a lower rate for wound infections and local complications. These effects remained robust after a multivariate adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
1
19
0
4
Order By: Relevance
“…Some researchers have suggested that specific formulae, generally referred to as immuno-nutrition including high amounts of arginine, glutamine, branched chain amino acids, n-3 fatty acids, and nucleotides, may provide further benefit for infection patients also including COVID-19 patients. Yet, such treatments were not studied in the EFFORT trial, nor to our knowledge, in any other trial [ [45] , [46] , [47] ]. Still, some data suggest that a diet enriched with eicosapentaenoic acid (EPA) and g-linolenic acid (GLA) may favorably reduce the pulmonary inflammatory response and support vasodilation and oxygenation in septic patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have suggested that specific formulae, generally referred to as immuno-nutrition including high amounts of arginine, glutamine, branched chain amino acids, n-3 fatty acids, and nucleotides, may provide further benefit for infection patients also including COVID-19 patients. Yet, such treatments were not studied in the EFFORT trial, nor to our knowledge, in any other trial [ [45] , [46] , [47] ]. Still, some data suggest that a diet enriched with eicosapentaenoic acid (EPA) and g-linolenic acid (GLA) may favorably reduce the pulmonary inflammatory response and support vasodilation and oxygenation in septic patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 Furthermore, in a retrospective study on 411 H&N cancer patients, preoperative immunonutrition was associated with a shorter length of hospital stay and a lower rate for wound infections and local complications, with more pronounced effects in those with previous RT and extensive surgery. 49 During CT-RT, a controlled, randomized, prospective, double-blind, multicenter study on 111 patients with H&N and esophageal cancer showed that functional capacity and nutritional status were maintained in those receiving an immuneenhanced supplement and reduced in controls receiving a standard enteral diet. 50 Furthermore, in a small pilot study conducted on 31 non-metastatic stage III or IV H&N cancer patients treated with concomitant CT-RT, immunonutrition provided orally during 5 days before each cycle of CT was shown to be associated with a favorable modulation of inflammatory and oxidative status, and a low incidence of severe acute mucositis was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Arg is a semi-essential amino acid that has positive effects on immune function and reparative collagen synthesis, and it is thought to be an enhancer of T-cells [34,35]. Omega-3 fatty acids have anti-inflammatory effects that can promote wound healing, and enhance the adaptive immune response [36].…”
Section: Discussionmentioning
confidence: 99%